Art education as interdisciplinary link and extension action - Zamberlan dos Santos, Nara Rejane; Machado, Amanda; Batista Cordeiro, Elaine (Guará Journal, 2016)
An extension action was taken in a public school for students to stimulate children to come up with environment from your school imagination. The development took place through lectures, drawings, models and production of ornamental pieces with recycled materials. The results showed students interested by an adequate school space their ages and needs.